PENGARUH PERSEPSI HARGA, PROMOSI PENJUALAN, DAN KUALITAS PELAYANAN DALAM MENCIPTAKAN LOYALITAS PELANGGAN - Dela Isnaeni Rachmawati; Jaenudin Jaenudin (SMART Management Journal, 2022)
This study aims to determine the effect of price perception, sales promotion, and service quality in creating customer loyalty. This study uses a quantitative approach with descriptive methods, quantitative descriptive is a type of research to analyze data by describing or describing the data that has been collected. The instrument in this study used a questionnaire and the data analysis technique in this study used an instrument test, analysis requirements test, and hypothesis testing, and the method used was the multiple linear analysis methods. The results of this study indicate that: (1) price perception has a positive and significant effect on customer loyalty, (2) price sales promotions have a positive and significant effect on customer loyalty, (3) service quality has a positive and significant effect on customer loyalty, (4) perception price, sales promotion, and service quality together have a positive and significant effect on customer loyalty.